Effects of extraction methods on yam (Dioscorea alata) starch characteristics - Daiuto, T.; Cereda, M.; Sarmento, S.; Vilpoux, O. (Wiley-Blackwell, 2005)
Starch extraction from roots and tubers uses grating with water and sieves to separate the starch slurry from residual mass. The starch is recovered by decantation or centrifugation. The yam starch extraction is difficult due to high viscosity of the slurry caused by non-starch polysaccharides (NSP). The establishment of an efficient extraction process may turn yam into a competitive raw material. In this paper Dioscorea alata starch extracted by four methods was characterized in order to establish the impact of treatments. When the tubers were digested with an aqueous oxalic acid/ammonium oxalate (OA/AO) 1/1 solution, it was easier to separate the starch slurry from residual mass, because viscosity was reduced. For all the others methods tested, the viscosity remained almost the same. The nitrogen present in yam tubers was removed during the different extractions to a different extent. The largest nitrogen reduction was observed with ONAO followed by the control (water). The spectrum of starch granules sizes obtained also varied according to the treatment. Results proved that NSP carries small starch granules over to the waste water. The smaller starch granules diameter varied from 1.9 mu m (OA/AO extraction) to 13.5 mu m (water and pectinase extractions). The larger diameter varied from 41.0 mu m (NaOH treatment) to 67.7 mu m (ONAO). All starches extracted showed a RVA behavior in agreement with literature for yam starch, but with small differences due to the influence of methods. ONAO extraction showed the best recovery (18 g of starch/100 g tuber yam) and granular variation but it interfered with the rheological behavior of starch.
Keywords: yam; starch extraction; properties; granulometry